A rare cause of effusive–constrictive pericarditis. (26th June 2021) - Giordani, Andrea S.; De Gaspari, Monica; Baritussio, Anna; Rizzo, Stefania; Carturan, Elisa; Basso, Cristina; Napodano, Massimo; Testolin, Luca; Marcolongo, Renzo; Caforio, Alida L.P.
Abstract: Effusive–constrictive pericarditis (ECP) is an uncommon diagnosis, frequently missed due to its heterogeneous presentation, but a potentially reversible cause of heart failure. A 62‐year‐old Caucasian male presented with remittent right heart failure and mild–moderate pericardial effusion. Following an initial diagnosis of idiopathic pericarditis, indomethacin was started, but the patient shortly relapsed, presenting with severe pericardial effusion and signs of cardiac tamponade, requiring pericardiocentesis. ECP was diagnosed on cardiac catheterization. Cardiac computed tomography showed non‐calcified, mildly thickened and inflamed parietal pericardium. Pericardiectomy was performed with symptoms remission. On histological examination of pericardium, chronic non‐necrotizing granulomatous inflammation was noted. Polymerase chain reaction assay was positive for non‐tuberculous mycobacteria. This case represents a rare finding of ECP with unusual presentation due to atypical mycobacteriosis in a non‐immunocompromised patient and in a non‐endemic area. Pericardiectomy can be an effective option in cases unresponsive to anti‐inflammatory treatment, even in the absence of significant pericardial thickening or calcification.